Simulasi CFD Berbasis Single Particle pada Proses Fast Pyrolysis Biomassa Kulit Kopi Menggunakan Reaktor Screw untuk Optimasi Produksi Gas (Mars: Jurnal Teknik Mesin, Industri, Elektro Dan Ilmu Komputer, 2026)
Coffee husk is an agro-industrial waste with significant potential to be utilized as a renewable energy source through the fast pyrolysis process. This study aims to analyze and optimize gas production from the fast pyrolysis of coffee husk biomass using a screw reactor through single-particle-based Computational Fluid Dynamics (CFD) simulations. The simulations were conducted by varying the operating temperature at 500°C, 600°C, and 700°C to examine pressure distribution, heat transfer, particle temperature, and the formation of pyrolysis products, namely bio-oil, biogas, and biochar. The modeling was performed using COMSOL Multiphysics 6.2 with a numerical approach to represent thermal phenomena and biomass decomposition reactions during the pyrolysis process. The simulation results indicate that increasing temperature significantly affects the rate of heat transfer and the temperature distribution of coffee husk particles. At 600°C, heat transfer and temperature distribution are more uniform compared to 500°C, although heating at the particle core is not yet fully optimal. The pressure distribution shows a stable flow of pyrolysis gas from the bottom to the top of the reactor. In terms of products, increasing temperature leads to a reduction in biochar and bio-oil formation due to the occurrence of secondary reactions, while biogas production increases. The highest gas production is achieved at 700°C, indicating the most optimal condition for maximizing gas yield from fast pyrolysis. Therefore, single-particle-based CFD simulation can be used as an effective tool to understand pyrolysis mechanisms and optimize process parameters in a screw reactor.